2020
DOI: 10.1038/s41598-020-61837-y
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and modelling of deep sea sediment plumes and implications for deep sea mining

Abstract: Deep sea mining concerns the extraction of poly-metallic nodules, cobalt-rich crusts and sulphide deposits from the ocean floor. The exploitation of these resources will result in adverse ecological effects arising from the direct removal of the substrate and, potentially, from the formation of sediment plumes that could result in deposition of fine sediment on sensitive species or entrainment of sediment, chemicals and nutrients into over-lying waters. Hence, identifying the behaviour of deep-sea sediment plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 39 publications
2
52
0
Order By: Relevance
“…However, the amount of re-mobilised sediment that does not go into resuspension was found to be notably larger. A recent plume study by Spearman et al (2020) carried out on a seamount near the Canary Islands, showed that a release rate of 0.2 kg s −1 of sediment into the water led to a maximum SSC similar to our measurements. Using a different release rate results in a weaker correlation between modelled and sensor data.…”
Section: Sediment Release Ratesupporting
confidence: 89%
See 2 more Smart Citations
“…However, the amount of re-mobilised sediment that does not go into resuspension was found to be notably larger. A recent plume study by Spearman et al (2020) carried out on a seamount near the Canary Islands, showed that a release rate of 0.2 kg s −1 of sediment into the water led to a maximum SSC similar to our measurements. Using a different release rate results in a weaker correlation between modelled and sensor data.…”
Section: Sediment Release Ratesupporting
confidence: 89%
“…To date, knowledge of deep-sea sediment transport from numerical modelling is limited to a few studies that were carried out based on accompanied observations e.g., in Pacific Ocean (Jankowski et al, 1996;Nakata et al, 1997;Jankowski and Zielke, 2001;Roliniski et al, 2001;Schriever and Thiel, 2013;Aleynik et al, 2017) or in the vicinity of Canary Islands (Spearman et al, 2020). Many modelling efforts have been associated with a particular resuspension experiment and were developed commercially with a restricted access to the underlying data (personal communication with A.J.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on this understanding, we use the validated DP1 dynamic plume model to provide realistic source conditions for a regional-scale numerical simulation of an ambient plume from a commercial nodule mining operation in the CCFZ. We used the TELEMAC model (see "TELEMAC numerical model" section), which is an established model that has previously been used for case-studies of deep-sea mining sediment plumes 45,46 , to hindcast ocean conditions and the associated transport and mixing. The goal of the TELEMAC model is not to predict the exact ocean conditions at a given date, but to provide physically reasonable ocean dynamics as the basis for a plausible model of a midwater ambient plume.…”
Section: Discharge Pipe Connectorsmentioning
confidence: 99%
“…As the fate of the plume is subject to local environmental conditions, effects are likely much farther-reaching and could cover more than twice the area disturbed (Gjerde et al 2016). This limitation has been recognised and, in response, a number of recent studies have modelled sediment plume dynamics from ship discharges (Rzeznik et al 2019), laboratory experiments (Gillard et al 2019) and in situ seabed disturbances (Kulkarni et al 2018, Spearman et al 2020. Whilst this modelling is a step in the right direction, these recent experiments do not assess biological responses.…”
Section: Limitations Of Simulated Mining Experimentsmentioning
confidence: 99%